2011
DOI: 10.1200/jco.2010.32.5167
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health and Supportive Care Needs of Long-Term Cancer Survivors: A Questionnaire Survey

Abstract: The findings suggest a majority of long-term breast, colorectal, and prostate cancer survivors who have no signs of recurrence report good health and do not have psychological morbidity or large numbers of unmet supportive care needs. A minority of long-term survivors may benefit from ongoing support. The identification and support of those long-term survivors with ongoing needs is a key challenge for health care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
134
7
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 42 publications
12
134
7
4
Order By: Relevance
“…The breast cancer patients in the present study reported lower psychological unmet needs than those reported in Western research (Whelan et al, 1997;Hodgkinson et al, 2007;Armes et al, 2009;Harrison et al, 2011;Lam et al, 2011;Schmid-Büchi et al, 2011). It should be noted that the women in the present study had completed their initial course of treatment and were four to six months post diagnosis.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The breast cancer patients in the present study reported lower psychological unmet needs than those reported in Western research (Whelan et al, 1997;Hodgkinson et al, 2007;Armes et al, 2009;Harrison et al, 2011;Lam et al, 2011;Schmid-Büchi et al, 2011). It should be noted that the women in the present study had completed their initial course of treatment and were four to six months post diagnosis.…”
Section: Discussioncontrasting
confidence: 51%
“…This is similar to Asian studies conducted in Taiwan (Liao et al, 2012), Japan (Nakaguchi et al, 2013) and Hong Kong Li et al, 2013) wherein breast cancer patients reported high rates of unmet supportive care needs, particularly in the informational domain. This contrasts with research conducted in Western countries, including Switzerland (Schmid-Büchi et al, 2012), Australia (Hodgkinson et al, 2007;McDowell et al, 2010), Germany (Lam et al, 2011), England (Armes et al, 2009;Harrison et al, 2011) and Canada (Whelan et al, 1997), wherein breast cancer patients have moderate levels of supportive care needs and unmet needs were highest in the psychological domain. Differences in supportive care needs have leaded others to conclude that supportive care needs are culturally dependant (Lam et al, 2011).…”
Section: Discussioncontrasting
confidence: 42%
“…For our two studies (Kanera, Bolman, Mesters, et al., 2016; Willems et al., 2016a), the validated CaSUN was regarded as the most appropriate general questionnaire to specifically investigate the unmet needs of cancer survivors (Bender et al., 2012; Brennan, Butow, Spillane, & Boyle, 2016; Geller et al., 2014; Harrison et al., 2011; Hodgkinson, Butow, Fuchs, et al., 2007; Hodgkinson, Butow, Hunt, et al., 2007; Rowlands, Janda, McKinnon, Webb, & Beesley, 2015; Smith et al., 2013; Urbaniec, Collins, Denson, & Whitford, 2011). Therefore, the CaSUN was translated into Dutch.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported that breast cancer survivors displayed poorer quality of life than control groups 15,21,[25][26][27] , whereas other authors have not 23,24,26,28,29 .…”
Section: Introductionmentioning
confidence: 99%